PPE Education to Reduce the Risk of Workplace Accidents in The Furniture Industry - Zahra, Alya Sofia; Hasibuan, Athiyyah Qurrotu’ain; Anisa, Aza Putri; Amrullah, Farhan Dani; Rahma, Fitra Aulia; Fathiyah, Nisrina Nur; Annisa, Nurul; Rachmawati, Putri (Journal of Safety Education, 2024)
Occupational safety and health is an important aspect in the industrial world, including the furniture industry. If a company implements the Occupational Health and Safety well, it can reduce the risk of work accidents, thereby increasing work productivity. Work accidents can occur due to workers’ negligence or suboptimal implementation of the Occupational Health and Safety System. To reduce the risk of work accidents, a risk analysis is carried out, which is one part of risk management. One of the risk analyses that can be done is by using the Failure Mode and Effect Analysis (FMEA) method. Risk identification in the furniture industry is based on field reviews, which then assess the severity (S), occurrence rate (O), and detection level (D). Then the assessment results are sorted to determine the highest Risk Priority Number (RPN) value variable. In the furniture production process, there are various potential hazards, with the highest RPN found in the cutting process, where a machine incident occurred with an RPN value of 120. The severity factor is given a value of 6 because the error leads to torn injuries and equipment damage, so it must be handled immediately, and there is the repair of the damage. One effort to reduce the risk of work accidents is to provide PPE at work.